2010
DOI: 10.1039/c0cc03689g
|View full text |Cite
|
Sign up to set email alerts
|

Helical polymers based on intramolecularly hydrogen-bonded aromatic polyamides

Abstract: Inspired by arylamide-based oligomeric foldermers that are stabilized by intramolecular hydrogen bonding, a series of polyamides with intramolecular hydrogen-bonding motifs were synthesized via polycondensation reactions. These polymers can fold into helical conformation different from their linear control. The chirality of helical conformation can further be tuned via acid-base complexation using chiral residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
(7 reference statements)
1
24
0
2
Order By: Relevance
“…The observation of cotton effects in CD spectrum suggest the helical conformation of CPILs in aqueous which is further supported by the previous literature reports. 24,29,60,63 In our studies, we have observed the positive and negative cotton effects in the CD spectra of CPILs. The CPILs possessing L-and D-amino acids as counter anions show completely opposite CD signals as shown in Figure 2.…”
Section: Poly(vieim)-d-pr Poly(vieim)-l-his Poly(vieim)-d-his Polysupporting
confidence: 58%
See 2 more Smart Citations
“…The observation of cotton effects in CD spectrum suggest the helical conformation of CPILs in aqueous which is further supported by the previous literature reports. 24,29,60,63 In our studies, we have observed the positive and negative cotton effects in the CD spectra of CPILs. The CPILs possessing L-and D-amino acids as counter anions show completely opposite CD signals as shown in Figure 2.…”
Section: Poly(vieim)-d-pr Poly(vieim)-l-his Poly(vieim)-d-his Polysupporting
confidence: 58%
“…This strong cotton effects in the CPILs CD spectra evidences the chiral orientation of polymer chain in a helical confirmation as suggested by previous reports. 24,29,60,63 The first and second positive cotton effects in CD spectrum of CPILs were observed at 213 and 195 nm, whereas the first and second negative cotton effects in CD spectrum of CPILs were observed at 214 and 196 nm, respectively. The UV CD studies clearly suggest the helicity in these chiral PILs.…”
Section: Poly(vieim)-d-pr Poly(vieim)-l-his Poly(vieim)-d-his Polymentioning
confidence: 96%
See 1 more Smart Citation
“…Trying to mimic nature, many researches have been directed into developing artificial helical polymers. Lu et al [158] synthesized a series of polyamides with intramolecular hydrogen-bonding motifs that can fold into helical conformation (Scheme 42, P69). For that purpose, they prepared polymer P69-1 from methoxy-substituted m-amino benzoic acid and compared it with an analogous polymer from m-amino benzoic acid, with a similar structure but unable to form multiply centered intramolecular H-bonds.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Synthetic polymers often adopt secondary structures guided by the make‐up of their monomer units and pendant side‐chains . Poly(methylmethacrylate)s containing bulky pendant units, synthesized mainly via anionic polymerization or uncontrolled radical polymerization, are known to form rigid, helical structures .…”
Section: Introductionmentioning
confidence: 99%